(untitled) (Zaporizhzhia Historical Review, 2021)
The purpose of the given historiographic research is to find out the conceptual base and thematic directions of the western historiography problems of collectivization and dekulakozation, since in 1991, the crash of the USSR has caused original changes in the world historiographic discourse.